2014
DOI: 10.5901/mjss.2014.v5n4p263
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Measure of Productive Organisational Energy in the South African Context

Abstract: Despite the inroads that are currently being made into research in the area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…These results are divergent from the construction and validation study of the original instrument (Cole et al, 2012), in which an internal structure of three first-order factors and one secondorder factor was obtained. However, the data found here are consistent with the results observed by Cuff and Barkhuizen (2014) in their validation study to the South African context. A possible explanation for the differences between the final model of the original study and the model currently obtained may be the fact that the two studies were conducted in different cultures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are divergent from the construction and validation study of the original instrument (Cole et al, 2012), in which an internal structure of three first-order factors and one secondorder factor was obtained. However, the data found here are consistent with the results observed by Cuff and Barkhuizen (2014) in their validation study to the South African context. A possible explanation for the differences between the final model of the original study and the model currently obtained may be the fact that the two studies were conducted in different cultures.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the instrument development study, the scale had its validity evidence tested only in one more context, the South African context, in a sample composed of 304 workers. In the study to search for validity evidence, Cuff and Barkhuizen (2014) conducted Exploratory Factor Analysis to test the structure of the instrument in that context. The results showed that the three-factor structure (affective energy, cognitive energy, and behavioral energy) was appropriate for the data, with all 14 items retained.…”
mentioning
confidence: 99%
“…Schippers & Hogenes (2011) defined organizational energy as: the results of building good relationships between workers, dependent on physical and mental health, and seeking to reduce the depletion of workers' capabilities, and achieve higher productivity. Cuff and Barkhuizen (2014) believes that it is the ability to combine different human energies (cognitive energy, behavioral energy, and emotional energy) in order to achieve the desired goals pursued by a successful organization. Organizational energy refers to the level of individual participation more than just doing a job, and it also refers to the effort exerted, so both are important for the doer, and for reaching meaningful work, so people who demonstrate meaningful work have two attributes: focus and energy (Bruch & Ghoshal, 2003).…”
Section: Organizational Energymentioning
confidence: 99%
“…(Cole et al, 2012;Alexiou et al, 2019;Grobler & Grobler, 2021) . (Cuff & Barkhuizen, 2014;Baker, 2019) . ً ‫ًال‬ ‫اُؼبؽل٤خ‬ ‫اُطبهخ‬ ‫رؼيى‬ ‫ُٝنُي،‬ ٖٓ ‫األٛلاف‬ ‫اُ٘لَ٤خ‬ ‫اُلوك٣خ‬ ‫ٝاألٛلاف‬ ‫اُغٔبػ٤خ‬ ‫اُز٘ظ٤ٔ٤خ‬ ( Schiuma et al, 2007 ) ‫كٜ٢‬ ‫ٝثبُزبُ٢‬ ، ‫ٝاُغٔبػ٢‬ ‫اُلوك١‬ ‫األكاء‬ ‫َٓزٞ٣بد‬ ‫ك٢‬ ‫رإصو‬ (Taylor, 2015) .…”
unclassified